Association between soluble immune mediators and tumor responses in patients with nonsmall cell lung cancer treated with anti‐PD‐1 inhibitor. Issue 5 (12th November 2018) - Matsuo, Norikazu; Azuma, Koichi; Hattori, Satoshi; Ohtake, Junya; Kawahara, Akihiko; Ishii, Hidenobu; Tokito, Takaaki; Yamada, Kazuhiko; Shibata, Yuji; Shimokawaji, Tadasuke; Kondo, Tetsuro; Kato, Terufumi; et al.
Abstract : Although programmed death (PD)‐1 immune checkpoint therapies target the immune system, the relationship between inflammatory factors and the clinical outcome of anti‐PD‐1 therapy for nonsmall cell lung cancer (NSCLC) is not fully understood. Here we examined the association between soluble immune mediators and the outcome of treatment with PD‐1 inhibitors in patients with advanced/recurrent NSCLC. In two independent cohorts, we assessed the levels of 88 different soluble immune mediators in peripheral blood before and after anti‐PD‐1 treatment, and evaluated their associations with clinical outcomes. In the training cohort, the plasma levels of chitinase 3‐like‐1 and GM‐CSF before treatment ( p = 0.006 and p = 0.005, respectively) and changes in the plasma levels of CXCL2, VEGF, IFNα2, and MMP2 after treatment ( p < 0.001, p = 0.019, p = 0.019, and p = 0.012, respectively) were significantly correlated with PFS. The change in the plasma CXCL2 level was also significantly associated with treatment‐related AEs ( p = 0.017). In the validation cohort, however, only the changes in the plasma levels of CXCL2 and MMP2 after treatment were associated with PFS ( p = 0.003 and p = 0.006, respectively), and these changes were maintained during the course of anti‐PD‐1 therapy in patients who showed better clinical outcomes, even in those with tumor pseudoprogression. Since CXCL2 and MMP2 can be easily measured by minimally invasive blood sampling, they could be useful for monitoring of clinical outcomes in NSCLC patients receiving PD‐1 inhibitor therapy. Abstract : What's new? Programmed death (PD)‐1 immune checkpoint inhibitors are used clinically for the treatment of advanced nonsmall cell lung cancer (NSCLC). Little is understood, however, about associations between immune mediators and clinical outcome in anti‐PD‐1‐treated NSCLC patients. Here, in two independent NSCLC cohorts, progression‐free survival was significantly associated with decreasing levels of the cytokine CXCL2 and increasing levels of matrix metalloproteinase‐2 (MMP2) after anti‐PD‐1 treatment. Over the course of anti‐PD‐1 therapy, these changes were associated with improved clinical outcome. CXCL2 and MMP2 can be measured by minimally invasive procedures, making them promising tools for clinical outcome monitoring in anti‐PD‐1‐treated NSCLC patients.